Validity of factor structure of the TVET graduates's job performance inventory - Zulkipli, Inas; Nordin, Mohamad Sahari; Ismail, Nik Ahmad Hisham (2013)
The purpose of this study was to empirically test the Malaysian Technical and Vocational Education Training (VTET) Graduates’ Job Performance inventory. The study involved 287 respondents consisting of job supervisors of the TVET graduates. They were required to respond to a 5-point Likert scale questionnaire. The inventory originally consisted of 29 items with two sub-scales; task performance and contextual performance. An exploratory factor analysis was conducted with suggested a three-dimensional construct for the instrument with high measures of reliability. The data were further analyzed using confirmatory factor analysis. The revised measurement model supported the adequacy of a three-factor measure with each indicator rendered statistically and practically significant loading. The factors were moderately correlated with each others. Divergent validity and convergent validity were supported. Thus, the three-factor model that represents Malaysian TVET Graduates Job Performance inventory is construct-valid. The practical implications of the finding are discussed.